Transition Metal Dialkyldithiocarbamates and Their Antifungal Activity - Arora, Anupma; Sud, Dheeraj; Sharma, J.R.; Arora, C.L. (Asian Journal of Chemistry, 2010)
Transition metal dialkyldithiocarbamates [ (R2NCS2)nM; R2 = Me2 or Et2 and M = V, Mo, W and Pt] complexes were prepared by the reaction of metal chloride MCln; n = 3, M = V, W and n = 4, M = Mo, Pt with sodium dialkyldithiocarbamate, [ R2NCS2Na ; R2 = Me2 or Et2] in dichloromethane/water (1 : 1) mixture. The metal complexes were characterized by elemental analysis, solubility, conductance and infrared spectral studies. The various synthesized complexes along with their parent salts were screened for their fungitoxicity under in vitro conditions against the three phytopathogenic fungi viz. Alternaria alternata, Fusarium oxysporum and Colletotrichum capsici by spore germination inhibition technique. All the complexes exhibit antifungal activity to varying extents.